Plumb-- painting, somatics, and generosity : a thesis presented in partial fulfilment of the requirements for the Masters degree (Fine Arts) at Massey University, Wellington, New Zealand - Luxton, Colin (Massey University, 2012)
This exegesis explores the role of a “transverse” body in artistic practice, concentrating specifically on painting as a common space or index that links the awareness of the artist and the awareness of the viewer. The central premise of a bodily “transverse” quality draws from the philosophy of phenomenology—in particular the writings of Merleau-Ponty and Levinas—but also takes its cue from Dance practice and the writings and legacy of Antonin Artaud. The ways in which we participate in social space through our bodies can be seen in an articulate legacy of “visceral” art that surfaces throughout the history of figuration. This visceral nature that art invokes or signifies has been observed in art that tackles (among other things) traumatic experience and the ontology of the other. What can be seen as a kinaesthetic mode of painting (and art in general) is invariably couched within cultural contextual frameworks of the time.
Keywords: Colin Luxton; Painting; Philosophy